WASTING AWAY – SUPERIOR MESENTERIC ARTERY SYNDROME IN A YOUNG GIRL – A CASE REPORT - Rehman, Aisha; Shah, Jamal; Naeem, Awais; Naim, Fahad (Journal of Postgraduate Medical Institute, 2022)
The case of an 18-year-old girl with Superior Mesenteric Artery syndrome is presented here. She presented to us with complaints of anorexia, nausea, vomiting, and weight loss for the past year. She was cachectic and volume-depleted. All investigations and preliminary imaging were inconclusive. Upper GI endoscopy revealed normal structure up to the second part of the duodenum. Contrast-enhanced Computerized Tomography of the abdomen and pelvis did not reveal any intra- or extra-luminal pathology. The patient was unwilling to undergo surgical correction and opted for conservative treatment. This case highlights the importance of considering SMA syndrome in the differential diagnosis of patients presenting with anorexia and weight loss and emphasizes the changing epidemiology of SMA syndrome.